300-yard shuttle run test performance and high-intensity training intervention - Ruzic, L.; Sporis, G.; Leko, G. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Soccer is a predominantly aerobic game (2,5) and anaerobic energy is essential to performance in sprints, high intensity runs and duel plays; all of which may contribute to the final outcome of the game (4). The purpose of this study was to evaluate changes in anaerobic endurance in elite First league soccer players throughout two consecutive seasons, in two phases, with and without high-intensity situational drills. Eighteen soccer players were tested prior to and following the 8-week summer conditioning and again in the next season. Anaerobic endurance was tested at the beginning and end of the preparation period using a 300-yard shuttle run test (1, 3). The measured variables included 300-yard shuttle run test, maximal heart rate and maximal blood lactate at the end of the test. During the first phase of the study the traditional sprint training was performed only 2x wk and consisted of 15 bouts of straightline sprinting. In the second year the 4x4 min drills at an intensity of 90 - 95% of HRmax, separated by periods of 3 min technical drills at 55 - 65% of HRmax were introduced. Statistical significance was set at P 0.05. The traditional conditioning program conducted during the first year of the study did not elicit an improvement in anaerobic endurance as recorded in the 300-yard shuttle run test. The fact that the18 players who were the subjects during the first year stayed with the team in the second season enabled us to continue the study. At the start of the 2nd phase the initial measurements were repeated on the same subjects and no significant differences were recorded in any of the variables between the initial measurements in 2002 and 2003, which was a necessary precondition for the study to continue. Following the intervention, the overall test running time improved significantly (55.74+/-1.63 s vs. 56.99+/-1.64 s; p<0.05) with the maximal blood lactate at the end of the test significantly higher (15.4+/-1.23mmol/L vs. 13.5+/- 1.12 mmol/L; p<0.01). The coefficient alpha for 300-yards shuttle run test was 0.96 while the test re-test method showed high ICC values (ICC = 0.93; range 0.83 - 0.97; p < 0.0031). No significant differences between the tests were observed in maximal achieved heart rate, body fat and body weight. The calculated statistical power for this study was 0.168.As a result, this study showed some indication that situational high-intensity task training was more efficient than straight-line sprinting in improving anaerobic endurance measured by the 300-yard shuttle run test.